Tradisi Fallohe dalam masyarakat Bulupoddo: Jejak spiritualitas lokal dan roh leluhur di tengah perspektif keagamaan - Musdalifah Musdalifah; Mifta Alchaerah; Tri Wanda Putri (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2026)
The goal of this study is to explore the Fallohe tradition as a reflection of local spirituality and ancestral spirits in the Bulupoddo community, especially in light of modern religious views. This research used a qualitative method, gathering data through phone interviews with several key informants who understand and participate in the Fallohe tradition. The findings show that the community sees Fallohe as an ancestral heritage that carries spiritual and cultural values, which they still preserve today. People believe this tradition brings blessings, protection, and prosperity in many areas of life. Additionally, Fallohe is viewed not just as a ritual practice, but also as a symbol of the connection between humans, ancestral spirits, social life, and cultural values passed down through generations. Despite the rise of modern religious ideas, the Fallohe tradition reflects the ongoing interaction between local spirituality, ancestral culture, and the community's understanding of religion.